Fusarium isolates in burn-injured patients: Clinical characteristics and susceptibility patterns - Robyn Stoianovici; Sierra Young; Jeremiah J. Duby; Naomi Hauser; Erin Louie (Burns Open)
Introduction/Objective: Fusarium species are ubiquitous in the environment and can cause opportunistic infection in burn-injured patients. The purpose of this retrospective cohort observational study is to characterize Fusarium susceptibilities, antifungal and surgical management, and the effect on survival in this patient population. Methods: All burn ICU patients with a positive Fusarium culture were retrospectively identified between November 2017 to June 2023 at a regional burn center. Demographic, clinical, and microbiologic susceptibility data was collected from the electronic medication record. Results: Eighteen patients with positive Fusarium wound cultures were included. The median age was 35 (32–41) years and 28 % were female. The average %TBSA was 55 ± 23 % and r-Baux score of 93 ± 22. The most common mechanism of injury was thermal burn (17 patients, 94 %). This cohort experienced prolonged ICU [53 (46–95) days] and hospital [57 (48– 97) days] lengths of stay. The median time from burn injury to positive Fusarium cultures was 18 (14–24) days. Mechanical ventilation was common (94 %) and prolonged [42 (34–55) days]. Sixty percent of isolates resulted with a minimal inhibitory concentration (MIC) ≥ 16 mcg/ml for voriconazole and 93 % isolates resulted with an MIC < 1 mcg/ml for amphotericin B. All patients underwent surgical debridement for source control. Ten of 18 patients (55 %) with Fusarium-positive infections survived to hospital discharge. Infection complicated by multisystem organ failure and sepsis was the most common attributable cause of death (88 %). Conclusion: Patients infected with Fusarium were severely burned, critically ill, and exposed to prolonged mechanical ventilation and to central venous catheterization. The high mortality rate associated with Fusarium infection and prolonged time to antifungal susceptibility results emphasize the importance of appropriate empiric therapy.